Perancangan Sistem Manajemen Keamanan Pada Rantai Pasok ISO 28000:2007 Di PT X - Jerim Renai Rumalutur; Jani Raharjo (Jurnal Titra, 2019)
This research is meant to explain the program of security supply chain management in order to get the certification of ISO 28000:2007 at PT. X. Security supply chain management system is used to assure the secure of the supply chain. The research at the PT. X is done by analysing the Gap Analysis between the company and the terms of the ISO 28000:2007. The research result shows us at 9.35% of compatibility with the ISO 28000:2007 terms and condition. The thesis result is going to be used to fix and develop the security supply chain management at PT. X. The development is going to be used to arrange the document to be suitable with the ISO 28000:2007 terms and condition. The systems are. The result of the final Gap Analysis shows at 69,16% of suitability with the ISO 28000:2007.